Estudo do confinamento com PRFC de pilares de concreto sujeitos a compressão excêntrica - Marques, Eduardo Alcino de Farias (2018)
Reinforced concrete structures must go through rehabilitation or a reinforcement process when they have inadequate levels in their safety and in the conditions of use of the construction. Reinforcement systems using carbon fiber reinforced polymer (CFRP) have been increasingly employed in Civil Construction due to their excellent mechanical properties, low self-weight and fast application. The objective of this work is to analyze through theoretical and numerical simulations, the confinement behavior of reinforced concrete columns with CFRP subjected to eccentric compression. In order to quantify the effects of the confinement of concrete columns by wrapping with CFRP, the results of these are compared with the results of the simple concrete and reinforced concrete columns. The Concrete Damaged Plasticity (CDP) is a model based on plasticity and material damage and is used for characterization of concrete in ABAQUS software. Initially, CDP is validated through the numerical example of the Foure Column and validated the carbon fiber modeling by the Wu and Jiang tests. The numerical models proved the efficiency of the reinforcement, evidencing the increase of the resistance capacity with the increase of the number of layers of carbon fiber. The theoretical models of the problem served as a reference and comparative for numerical models, obtaining similar values that prove their formulations. It was observed that in rectangular sections the confinement generated is smaller compared to circular section columns, so the adoption of rounding radius is suggested, thus increasing reinforcement efficiency.